Selected Aspects of Human Life in Civil and Criminal Law (University of Maribor Press, 2021)
The scientific monograph ’Selected aspects of human life in civil and criminal law’ comprises ten contributions. The authors analyse various aspects of the meaning of human life in the light of selected topics in civil and criminal law. The Slovenian and Turkish authors, aware of the importance and sensitivity of the overarching theme of the scientific monograph, provide an analysis of selected pressing topics (e.g. honour killing, disinheritance, crimes against life and limb, vulnerability of certain social groups (elder persons)) in the light of both national, as well as of international regulation and relevant case-law. The scientific monograph thus provides the reader with an insight into historical, current and future aspects of human life.